El engagement y la intención de rotación laboral en los colaboradores administrativos del Poder Judicial de la Corte Superior de Justicia de Loreto, Noviembre 2019 - Falcón Mendoza, Raquel (2022)
The collaborator who does not feel committed to the work they do and also little motivated has a great chance of leaving the job, which leads the institution to have additional costs due to what represents the learning curve of new collaborators. In this context, the investigation raises the following question: Is there a relationship between Engagement and the intention to rotate of the administrative collaborators of the Judicial Branch of the Superior Court of Justice of Loreto, November 2019? and as an objective to determine the relationship between the engagement and intention to rotate of the administrative collaborators of the Judicial Branch of the Superior Court of Justice of Loreto, November 2019; The research is correlational level, non-experimental design and transectional, the population is made up of 87 collaborators of the Superior Court of Justice of Loreto. The research determined a Spearman's Rho correlation coefficient of -0409 and a p of 0.000. Which indicates that there is a significant moderate indirect relationship. Similarly, the relationship between the dimension of engagement vigor and the intention to rotate is indirect moderately significant, the relationship between the dimension dedication and the intention to rotate is indirectly low significant and the relationship of the dimension absorption with the intention to rotate is indirect very low not significant in the administrative collaborators of the Judicial Branch of the Superior Court of Justice of Loreto, Iquitos 2021.